Influence of mixed aqueous solutions of polyhexamethylene guanidine hydrochloride and OP-10 on vegetable crop seeds (International Journal of Biology and Chemistry, 2018)
The effect of bactericidal and fungicidal polymer polyhexamethylene guanidine hydrochloride (PHMGH) and its mixture with non-ionic surfactant oxyethylated isooctylphenol (OP-10) on the germination of seeds of tomatoes, cucumbers and sugar beet was studied. PHMGH is known disinfectant. It is odorless, colorless, non-corrosive and non-toxic for humans, PHGMH can be applied to make an innovative product in the disinfection of plants and vegetables and preservation of food products, . Vegetable seeds were treated with aqueous solutions of PHMGH, OP-10 and mixed solutions of PHMGH/OP-10. Tests were made in relation to the growth and development of plants treated with bactericids. PHGMH (0.05 %) aqueous solution favors for cucumber seed growth (the germination percentage equals to 94 %), PHGMH/OP-10 complex (at a ratio of 1:1 at initial component concentrations equaled to 0.01%) for tomato seeds (90% ). The mixture of PHMG/OP-10 was effective on the growth and development for all of the studied vegetable crops (stem and leaf length). The effect of aqueous solutions of PHMGH, OP-10 and PHMGH/OP-10 on the content of chlorophyll in the leaves of the studied objects was studied. The increasing of chlorophyll amount was observed after treatment with PHGMH complexes that results in resistance of vegetables to action of environmental factors.